Upgrading of Resolution Elastic Neutron Scattering (RENS) - S. Magazù; F. Migliardo; M. T. Caccamo (Advances in Materials Science and Engineering)
An update of the Resolution Elastic Neutron Scattering (RENS) approach consisting in measuring the elastically scattered neutron intensity versus the instrumental energy resolution is presented. In particular it is shown that the measured elastic scattering law as a function of the logarithm of the instrumental energy of resolution gives rise to an increasing sigmoid trend whose inflection point can be connected with the system relaxation time. The validity of the RENS approach is supported by a numerical simulation, taking into account a Gaussian resolution function and a Lorentzian scattering law, and experimentally by integrated EINS and QENS measurements performed as a function of temperature on three homologous disaccharide/water mixtures showing different relaxation times. Furthermore, the most important advantages of the RENS approach are discussed; in particular, in comparison with QENS, the RENS approach requires a smaller amount of sample, which is an important point in dealing with biological and exotic systems, is not affected by the use of model functions for fitting spectra, and furnishes a direct access to the system relaxation time.